Podrobnosti . Podrobnosti . Details . Подробности - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program on Russian-Kazakh relations. Featured in the program: Yeltsin, Boris Nikolayevich (President of the Russian Federation); Nazarbaev, Nursultan Abishevich (President of Kazakhstan); Chernomyrdin, Viktor Stepanovich (Prime Minister of the Russian Federation) Contributors: Dorenko, Sergei (Anchor) Передача об отношениях России и Казахстана. В программе участвуют: Ельцин, Борис Николаевич (Президент Российской Федерации); Назарбаев, Нурсултан Абишевич (Президент Казахстана); Черномырдин, Виктор Степанович (Председатель правительства Российской Федерации) Создатели: Доренко, Сергей (Ведущий/Ведущая)